AI-Based Digital Marketing Communication in Hotel Masa Inn Advertising - Wilbert William Jeff Jonathan; I Nyoman Indra Kumara (Journal of Innovative and Creativity, 2026)
This study examined the implementation of AI-based digital marketing communication in Hotel Masa Inn advertisements by applying the AIDA model. The study purpose was to analyze how artificial intelligence was utilized in digital advertising content to attract attention, build interest, stimulate desire, and encourage action among audiences on Instagram. This research employed a qualitative descriptive approach. Materials and methods involved field research conducted at Hotel Masa Inn, Kuta, Bali, using observation of Instagram content, in-depth interviews with hotel management, marketing staff, and consumers, as well as documentation of AI-based promotional materials. Data were collected through purposive sampling and analyzed inductively to capture patterns in audience responses and communication strategies across the AIDA stages. The results showed that AI played a strategic role throughout the communication process. At the attention stage, AI-supported visuals, voice-over narration, and consistent posting frequency successfully highlighted Balinese identity and created a calming first impression. At the interest stage, AI-generated storytelling maintained narrative consistency and strengthened audience engagement by presenting the hotel experience as warm and familiar. At the desire stage, AI-based copywriting emphasized comfort, historical value, and credibility, reinforced by organic audience testimonials that increased trust. At the action stage, clear AI-generated calls to action contributed to increased direct messages and story replies, indicating active audience responses. However, findings also revealed limitations, as some audiences perceived reduced emotional depth compared to human-generated communication. In conclusion, AI-based digital marketing communication at Hotel Masa Inn effectively supported all AIDA stages by enhancing message consistency, efficiency, and audience engagement. Nevertheless, human involvement remains essential to preserve emotional authenticity and strengthen long-term relationships with consumers